Level of Living In India An Analysis of Consumption and Poverty - Planning Commission (Planning Commission, 2000)
The report Level of Living in India: An Analysis of Consumption and Poverty provides a comprehensive evaluation of poverty, inequality, and consumption patterns in India based on the 1993–94 National Sample Survey (NSS) of over 115,000 households. It highlights regional, demographic, and socio-economic disparities, revealing that rural areas, Scheduled Castes and Tribes, larger households, and landless families face higher poverty levels. Traditional poverty metrics are critiqued, with the Squared Poverty Gap (SPG) proposed as a more nuanced measure, capturing both the depth and inequality of poverty. Findings indicate urban per capita consumption exceeds rural levels by 63%, while agricultural laborers and marginalized groups experience significantly lower living standards. Policy recommendations emphasize adopting SPG for targeting interventions, improving land distribution, and tailoring development programs to disadvantaged populations. The study underscores the need for evidence-based, context-sensitive strategies to reduce poverty and enhance living standards across India.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Level of Living; Poverty in India; Consumption Patterns; Squared Poverty Gap; Income Inequality; Rural-Urban Disparities; Household Size; Land Ownership; Socio-Economic Groups; National Sample Survey; Targeted Policy; Standard of Living